POLA ASUH AYAH TERHADAP ANAK PEREMPUAN DAN ANAK LAKI-LAKI KELUARGA PATRILINEAL - Katherine Paramitha Tjandra; Debora Basaria (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2018)
In Indonesia, there are 1128 ethnic groups that can be divided into 2 according to lineage system, that is matrilineal and patrilineal. In patrilineal families, family name, property and others are passed down through sons. The characteristics of patrilineal families showed bias and favor towards sons. The goal of this research is to provide a description of father’s parenting style towards daughters and sons in patrilineal families. This research used a descriptive research method with Baumrind’s parenting style as the grand theory. The data collection process starts from April till May to 201 fathers using a parenting style questionnaire from Tarumanagara University’s Department of Psychology. The result of this research shows that 84.6% of the total fathers applied the same kind of parenting style towards their sons and daughters. These fathers no longer differentiate between daughters and sons. 92.9% of these fathers applied authoritative parenting styles to both daughters and sons. A small portion of the participant, 15.4% of 201 participants applied different parenting style towards their daughters and sons. These fathers applied authoritative parenting style towards their daughters and permissive parenting style towards their sons.